1990
DOI: 10.1007/bf01806352
|View full text |Cite
|
Sign up to set email alerts
|

Cytometric and histopathologic features of tumors detected in a randomized mammography screening program: Correlation and relative prognostic influence

Abstract: Cytometric determination of S-phase fraction and ploidy type was performed on 430 tumors detected within a randomized trial of mammographic screening. The results were compared to several histopathologic features. A high S-phase fraction was estimated in tumors with a high grade of malignancy and other histopathologic findings related to rapid tumor progression, including lack of tubule formation, a high mitotic index, marked nuclear pleomorphism, multifocal cancer growth, tumor emboli in lymphatic and blood v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 37 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…The S phase percentage reflects the degree to which cells are proliferating and also serves as a marker for biologic activity by distinguishing tissues of high and low proliferation rates. Increased proliferative activity, as shown by the S phase percentage, has been associated with disease progression in breast cancer [17][18][19][20][21][22]. Similar to that reported for breast carcinomas, our data show that tissue containing benign atypical or hyperplastic proliferative changes or other benign histologic changes may be associated with either low or high cellular proliferative activity determined by S phase percentage.…”
Section: Discussionsupporting
confidence: 88%
“…The S phase percentage reflects the degree to which cells are proliferating and also serves as a marker for biologic activity by distinguishing tissues of high and low proliferation rates. Increased proliferative activity, as shown by the S phase percentage, has been associated with disease progression in breast cancer [17][18][19][20][21][22]. Similar to that reported for breast carcinomas, our data show that tissue containing benign atypical or hyperplastic proliferative changes or other benign histologic changes may be associated with either low or high cellular proliferative activity determined by S phase percentage.…”
Section: Discussionsupporting
confidence: 88%
“…Another method for assessing proliferative activity is the evaluation of mitotic activity. We are aware of seven studies that address this topic; all seven found a correlation between mitotic activity and SPF 18, 40–45. Nonetheless, mitotic activity was found to have independent prognostic value in studies46–48 as in the current one.…”
Section: Discussionmentioning
confidence: 77%
“…Flow cytometric measurement of DNA content per nucleus provides information both about DNA ploidy status and about proliferative activity as represented by the fraction of cells in the S-phase of the cell cycle, The prognostic value of DNA ploidy has been demonstrated in many studies (6,8,9,20,24,42), as has that of the S-phase fraction (SPF; 13,15,16,22,31,37), though others have failed to confirm the independent prognostic value of these variables (12,21,30). sults.…”
mentioning
confidence: 99%